Biocompacting livestock accelerate drowning of tidal salt marshes with sea level rise - Elschot, Kelly; Baptist, Martin J.; van Puijenbroek, Marinka E. B. (Frontiers in Marine Science, 2023)
A global concern for coastal ecosystems is the predicted rise in sea-level for which salt marshes must keep pace by increasing in surface elevation sufficiently. Variables that control this elevation change need to be identified to predict the adaptability of marshes to future sea-level rise. Many European marshes are grazed by livestock and these heavy grazers can biocompact the soil, a process often underestimated in studies assessing the long-term survival of marshes. We measured elevation changes for thirteen years in the field in grazed and non-grazed marshes. With a statistical model the most important factors controlling rates of surface elevation change were identified and provided the input for a mathematical model to study future elevation change of grazed and non-grazed salt marshes up to 2100 under three Sea Level Rise and sediment supply scenarios. We found that trampling by grazing cattle significantly reduced the annual rates of elevation gain from 11.9 mm yr-1 in the non-grazed marsh to 3.6 mm yr-1 in the grazed marsh. Next to biocompaction by livestock, precipitation deficit and extreme drought resulted in extra compaction. Our model results showed that cattle presence had a negative impact on the future adaptability of salt marshes to grow vertically for rising sea levels. Biocompaction reduced the total elevation change by 42% if the current linear SLR does not accelerate. For an accelerating and high SLR to 109 cm +NAP in 2100, biocompaction reduced elevation changes by 12% and the grazed marsh can no longer outcompete the rise in sea level from around 2050 onwards, compared to the non-grazed marsh. The grazed marsh will slowly drown but this will not lead to a significant change in vegetation composition yet. For an extreme SLR to 195 cm +NAP in 2100 the elevation changes in both the grazed and non-grazed marshes cannot keep pace with the rise in sea level and the marsh vegetation is expected to show regression to plants typical for a low marsh. A reduction in sediment supply will aggravate the effects of SLR and may result in highly increasing inundation frequencies and subsequent disappearance of the marsh vegetation.